Survey of demersal fishes from southern Saudi Arabia, with five new records for the Red Sea - Bogorodsky, Sergey V.; Alpermann, Tilman J.; Mal, Ahmad O.; Gabr, Mohamed H. (Zootaxa, 2014)
During a survey of demersal fishes of the southern Red Sea coast of Saudi Arabia off Jizan, 98 species were collected by trawling. Five of these represent new records for the Red Sea: Saurida longimanus, Dactyloptena gilberti, Jaydia novaeguineae, Pomadasys maculatus and Parapercis maculata. Additionally a specimen of the rare moray Gymnothorax reticularis, previously known from only three specimens, was collected. Records of two species, Parastromateus niger and Pseudorhombus arsius, that formerly were considered questionable, are confirmed by collection of new voucher specimens. Validity of Laeops sinusarabici is confirmed. This study documents parts of the diversity of the demersal fish communities on sandy areas of the southern Red Sea, but also emphasizes that a large proportion of this area has not been explored.